1989
DOI: 10.2466/pms.1989.69.3f.1371
|View full text |Cite
|
Sign up to set email alerts
|

Helping Orientations: Four Dimensions

Abstract: The underlying factor structure of four helping and coping orientations was investigated. The four orientations are the foundations of four models of helping and coping. Each model consists of a person's orientations toward helping behavior and the set of likely factors and behaviors related to the orientations. The orientations are believed to influence how a person interacts with others in a helping situation and how that person attempts to help himself (cope). Factor analysis in two studies supports the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 6 publications
2
26
0
Order By: Relevance
“…For the present study, the coefficient alphas were.79 for the Cause Scale and.76 for the Solution Scale. A 2-week test-retest reliability has been estimated at.86 for the Cause Scale and at.70 for the Solution Scale (Bailey & Hayes, 1998 (Michlitsch & Frankel, 1989). Construct validity evidence has been provided by Hayes and Wall (1998), who demonstrated that clinicians rated clients diagnosed with posttraumatic stress disorder as significantly less responsible for the cause of and solution to a problem in comparison to clients diagnosed with bulimia.…”
Section: Instrumentsmentioning
confidence: 98%
“…For the present study, the coefficient alphas were.79 for the Cause Scale and.76 for the Solution Scale. A 2-week test-retest reliability has been estimated at.86 for the Cause Scale and at.70 for the Solution Scale (Bailey & Hayes, 1998 (Michlitsch & Frankel, 1989). Construct validity evidence has been provided by Hayes and Wall (1998), who demonstrated that clinicians rated clients diagnosed with posttraumatic stress disorder as significantly less responsible for the cause of and solution to a problem in comparison to clients diagnosed with bulimia.…”
Section: Instrumentsmentioning
confidence: 98%
“…In addition, we used four items from a scale by Pascarella, Edison, Nora, Hagedorn, and Terenzini (1996) to gauge openness to diversity (α = .83). Third, an empowerment view of helping described beliefs about whether people can overcome their problems with the assistance of others; this five-item scale (α = .63) was taken from Michlitsch and Frankel (1989). Fourth, situational attributions for poverty convey a belief that poverty is caused by societal factors (e.g., poor school systems); we adapted this six-item scale (α = .72) from a survey by Feagin (1971).…”
Section: Primary Dependent Variablementioning
confidence: 99%
“…First, we used a short form of the social dominance orientation scale (Pratto, Sidanius, Stallworth, & Malle, 1994); this eight-item scale (α=.83) measures people's preference for and acceptance of inequality among social groups. A five-item self-generating view of helping scale (Michlitsch & Frankel, 1989) gauged people's beliefs that only individuals can help themselves overcome their problems (α = .70). Finally, belief in a just world describes the belief that good things happen to good people, and bad things happen to bad people.…”
Section: Primary Dependent Variablementioning
confidence: 99%
See 1 more Smart Citation
“…Their research finds that positive diversity experiences predict ESRo scores. The ESRo is comprised of seven subscales, which were presented in counterbalanced order: Responsibility for Improving Society (Nelson Laird, Engberg, & Hurtado, 2005), openness to Diversity (Pascarella, Edison, Nora, Hagedorn, & Terenzini, 1996), Empowerment View of Helping (Michlitsch & Frankel, 1989), Situational Attributions for Poverty (Feagin, 1971), Self-Generating View of Helping (Michlitsch & Frankel, 1989), Belief in a Just World (Dalbert, Montada, & Schmitt, 1987), and Social Dominance orientation (Pratto et al, 1994). The latter three subscales were reverse-coded, such that higher scores indicated greater equality and social responsibility orientation.…”
Section: Study Procedures and Materialsmentioning
confidence: 99%